Cross-cultural adaptation of the Posttraumatic Stress Disorder Checklist 5 (PCL-5) and Life Events Checklist 5 (LEC-5) for the Brazilian context - Lima,Eduardo de Paula (2016)
Abstract Objective: To describe the process of cross-cultural adaptation of the Posttraumatic Stress Disorder Checklist 5 (PCL-5) and the Life Events Checklist 5 (LEC-5) for the Brazilian sociolinguistic context. Method: The adaptation process sought to establish conceptual, semantic, and operational equivalence between the original items of the questionnaire and their translated versions, following standardized protocols. Initially, two researchers translated the original version of the scale into Brazilian Portuguese. Next, a native English speaker performed the back-translation. Quantitative and qualitative criteria were used to evaluate the intelligibility of items. Five specialists compared the original and translated versions and assessed the degree of equivalence between them in terms of semantic, idiomatic, cultural and conceptual aspects. The degree of agreement between the specialists was measured using the content validity coefficient (CVC). Finally, 28 volunteers from the target population were interviewed in order to assess their level of comprehension of the items. Results: CVCs for items from both scales were satisfactory for all criteria. The mean comprehension scores were above the cutoff point established. Overall, the results showed that the adapted versions' items had adequate rates of equivalence in terms of concepts and semantics. Conclusions: The translation and adaptation processes were successful for both scales, resulting in versions that are not only equivalent to the originals, but are also intelligible for the population at large.